2007
DOI: 10.1190/1.2756081
|View full text |Cite
|
Sign up to set email alerts
|

Estimating permeability of carbonate rocks from porosity and vp ∕ vs

Abstract: We present a method for predicting permeability from sonic and density data. The method removes the porosity effect on the ratio v p /v s of dry rock, and it addresses the specific surface as an indirect measure of permeability. We look at ultrasonic data, porosity, and the permeability of 114 carbonate core plugs. In doing so, we establish an empirical relationship between the specific surface of the solid phase ͑as calculated by Kozeny's equation͒ and v p /v s ͑linearly transformed to remove the porosity eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…The attenuation may reach a maximum for frequency in the order of 10 kHz, which is the domain of full waveform acoustic logging. It is the reason why several authors (Morlier and Sarda, 1971;Dupuy et al, 1973;Morlier, 1983, 2010;Klimentos and MacCann, 1990;Yamamoto, 2003;Fabricius et al, 2007; Figure 2…”
Section: From Laboratory Measurements To Geophysical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The attenuation may reach a maximum for frequency in the order of 10 kHz, which is the domain of full waveform acoustic logging. It is the reason why several authors (Morlier and Sarda, 1971;Dupuy et al, 1973;Morlier, 1983, 2010;Klimentos and MacCann, 1990;Yamamoto, 2003;Fabricius et al, 2007; Figure 2…”
Section: From Laboratory Measurements To Geophysical Measurementsmentioning
confidence: 99%
“…The objective of this borehole is to complement the geological and hydrogeological knowledge of this formation. This formation consists essentially of limestone deposited in a vast sedimentary platform (Ferry et al, 2007). The limestone facies, which vary from one borehole to another, are generally bio-detritic with reef constructions.…”
Section: Geological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In a vertical well, these tools are used to record five propagation modes: the refracted compression wave, the refracted To compute permeability from eq 1, it is necessary to measure the P-wave attenuation and the porosity of the formation and calculate the effective specific surface of the formation. Ida L. Fabricius et al ( 2007) have found that specific surface with respect to grain volume ( Sg) is apparently independent from porosity. In an attempt to remove the porosity effect on Vp/Vs and mimic a reflected φ vs log (Sg) trend, they propose to use the following relationship between porosity φ, Vp/Vs ( Vs: S-wave velocity) and Sg: …”
Section: Acoustic Loggingmentioning
confidence: 99%
“…His results on smectite and kaolinite aggregates suggest that the permeability of smectitic clays may be up to five orders of magnitude lower than that of kaolinitic clays with the same porosity, density, velocity or rock mechanical properties. Mari et al, (2011) described a methodology for obtaining a permeability log based on acoustic velocities V p and V s , porosity φ, P-wave attenuation and frequency, their calculation of the specific surface S of the formation was based on the relationship between porosity φ, V p /V s and S proposed by Fabricius et al (2007). Fabricius (2011) indicate that pore radius and thus permeability of shale in the depth interval of mechanical compaction may be predicted from porosity and sonic velocity.…”
Section: Introductionmentioning
confidence: 99%